Micropropagation and somaclonal variation in Iranian genotypes of garlic (Allium sativum L.) - Mohammad-Hossein Afzaz; Javad Mozafari; Sepideh Sanjari (PLoS ONE, 2025)
Garlic is an important bulb vegetable which is used for both culinary and medical purposes worldwide. In vitro propagation is considered a promising technic for production and conservation of disease-free garlic seed. The efficiency of in vitro culture was studied for micropropagation of native Iranian garlic genotypes. A factorial experiment based on a completely randomized design with three replications was conducted to optimize the in vitro culture media components for establishment, regeneration and conservation of four Iranian garlic genotypes. The highest number of bulblets were obtained and established on MS medium supplemented with 1.5 mgL-1 BA (benzyl adenine) + 0.5 mgL-1 IBA (indole-3-butyric acid) and 0.5 mgL-1 2-iP (2-isopentenyl adenine) + 0.25 mgL-1 NAA (naphthalene acetic acid), respectively. In the regeneration phase, however, the highest number of bulblets regenerated from in vitro grown plants on MS medium supplemented with 0.5 mgL-1 2-iP + 0.1 mgL-1 NAA. A drastic increase in bulblet formation was also observed on this culture medium during conservation phase. At least 20 bulblets were formed per each explant in all genotypes in the first subculture. Interestingly, the bulblet formation in the second subculture was 4–5 times more than the first subculture, indicating a very efficient regeneration rate in micropropagation of Iranian garlic genotypes. Moreover, RAPD (Randomly Amplified Polymorphic DNA) markers were used to evaluate the genetic stability in regenerated garlic plantlets. All fragments amplified by five RAPDs were the same in regenerated plantlets and their mother plants showing no somaclonal variation in micropropagated Iranian garlics. Our results indicated that in vitro protocols used in this study can provide an efficient system for regeneration and conservation of garlic germplasm in an in vitro gene-bank.